2018
DOI: 10.3847/1538-4357/aad69b
|View full text |Cite
|
Sign up to set email alerts
|

Transport of CO in Protoplanetary Disks: Consequences of Pebble Formation, Settling, and Radial Drift

Abstract: Current models of (exo)planet formation often rely on a large influx of so-called 'pebbles' from the outer disk into the planet formation region. In this paper, we investigate how the formation of pebbles in the cold outer regions of protoplanetary disks and their subsequent migration to the inner disk can alter the gas-phase CO distribution both interior and exterior to the midplane CO snowline. By simulating the resulting CO abundances in the midplane as well as the warm surface layer, we identify observable… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
159
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(176 citation statements)
references
References 99 publications
(150 reference statements)
12
159
1
Order By: Relevance
“…An elevated C/H gas ratio inside the CO snowline has long been predicted by models that include dust drift (Cuzzi & Zahnle 2004). More comprehensive simulations consider icy pebble formation, settling, and drifting with CO sublimation in a global disk setup (Booth et al 2017;Stammler et al 2017;Krijt et al 2018). In general, these models predict the C/H gas ratio inside the CO snowline can be elevated to 1-10 times of the initial ratio, while the detailed radial distribution depends on various parameters, including viscosity, diffusion rate, and disk sizes.…”
Section: Excess C/h As a Test Of Pebble Drift Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…An elevated C/H gas ratio inside the CO snowline has long been predicted by models that include dust drift (Cuzzi & Zahnle 2004). More comprehensive simulations consider icy pebble formation, settling, and drifting with CO sublimation in a global disk setup (Booth et al 2017;Stammler et al 2017;Krijt et al 2018). In general, these models predict the C/H gas ratio inside the CO snowline can be elevated to 1-10 times of the initial ratio, while the detailed radial distribution depends on various parameters, including viscosity, diffusion rate, and disk sizes.…”
Section: Excess C/h As a Test Of Pebble Drift Modelsmentioning
confidence: 99%
“…To make a more quantitative comparison, in Figure 4 we compare our best-fit models with predictions of Krijt et al (2018) . Krijt et al (2018) is the only 2-dimensional simulation that included the depletion of CO gas in the warm molecular layer outside the midplane CO snowline, which gives the closest theoretical comparison to our constraints on the C/H ratio in gas phase. Even the Krijt et al (2018) models were for a generic disk, our best-fit models match the general profile within a factor of two.…”
Section: Excess C/h As a Test Of Pebble Drift Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current chemical models indicate that an ISM level cosmic-ray ionization rate (10 −17 s −1 ) is essential for the chemical processing of CO (Reboussin et al 2015;Yu et al 2016;Eistrup et al 2018;Bosman et al 2018;Schwarz et al 2018Schwarz et al , 2019. But it is still unclear if the cosmic-ray ionization rate can reach that high level in 1-10 Myr old protoplanetary disks (Cleeves et al 2015).…”
Section: Co Depletion Mechanismsmentioning
confidence: 99%
“…Recently there have been multiple studies that have looked at the effect of disk evolution, especially the growth and drift of icy grains, at the effect this has on the gas-phase elemental abundances (Ciesla & Cuzzi 2006;Booth et al 2017;Stammler et al 2017;Bosman et al 2018;Krijt et al 2018;Booth & Ilee 2019). In general, it is found that enrichments above solar abundances in a certain element can happen just inside an ice line if radial drift is efficient and the ice line corresponds to a species that is an abundant ( 10%) carrier of that element.…”
Section: Enriching Jupiter With Nitrogenmentioning
confidence: 99%